2015
DOI: 10.1177/0049475515598464
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of rupture of the unscarred uterus and the related feto-maternal outcome: current scenario in a low-income country

Abstract: Training of traditional birth attendants for early referrals, screening for uterine anomalies by ultrasound in early pregnancy and counselling the women, especially multiparas and grand-multiparas are mandatory. Oxytocin should only be used for those if the doctor who prescribed its use stays with the patient continuously and stops oxytocics as soon as there are reasonable contractions. In emergency, the decision to delivery time should be less than 30 min. These are some ways through which a tragic event like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…The URIDA data analysis showed that UR is associated with previous uterine surgery. However, the present study's results agree with previous literature, 7 showing that UR can also occur in patients without previous uterine surgery. Even though associated with previous uterine surgery, the incidence did not increase with an increasing number of previous uterine operations, or if more than one type of operation was performed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The URIDA data analysis showed that UR is associated with previous uterine surgery. However, the present study's results agree with previous literature, 7 showing that UR can also occur in patients without previous uterine surgery. Even though associated with previous uterine surgery, the incidence did not increase with an increasing number of previous uterine operations, or if more than one type of operation was performed.…”
Section: Discussionsupporting
confidence: 92%
“…(5) the impact of fibroids on UR; (6) symptoms of UR; (7) length of hospitalization after UR; (8) complications of UR; (9) subsequent reproductive performance after UR, including fertility and the outcome of the following pregnancy; and (10) Apgar scores of the infant. This investigation was retrospective and not financially sponsored.…”
Section: Introductionmentioning
confidence: 99%
“…Uterine repair without tubal ligation was performed in only 5 women desiring future fertility. The percentage is much lower than 33.3% recorded in a study by Kankika et al but comparable with 5.9% in a study by Ahmed et al [28,31].…”
Section: Plos Onesupporting
confidence: 59%
“…15 Whereas case reported by Yi-Hui Lin et al in 2003 had a laceration about 1 cm in length over the left cornu. 19 Our case of posterior rupture of unscarred uterus is a very rare event and there has been hardly any case reported so far.…”
Section: Discussionmentioning
confidence: 89%
“…One study by Kanika Batra and et al in 2010-2012 shows there is 16.6% risk of rupture of uterus with labour induction. 19 Thus while augmenting labour in a patient we should always keep this catashtroph as complication in our mind even if the patient has no history of previous cesarean secton or mayomectomy.…”
Section: Discussionmentioning
confidence: 99%